2014
DOI: 10.1371/journal.pone.0103772
|View full text |Cite
|
Sign up to set email alerts
|

Genetic Structure of Qiangic Populations Residing in the Western Sichuan Corridor

Abstract: The Qiangic languages in western Sichuan (WSC) are believed to be the oldest branch of the Sino-Tibetan linguistic family, and therefore, all Sino-Tibetan populations might have originated in WSC. However, very few genetic investigations have been done on Qiangic populations and no genetic evidences for the origin of Sino-Tibetan populations have been provided. By using the informative Y chromosome and mitochondrial DNA (mtDNA) markers, we analyzed the genetic structure of Qiangic populations. Our results reve… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

2
34
1

Year Published

2015
2015
2021
2021

Publication Types

Select...
6
1
1

Relationship

3
5

Authors

Journals

citations
Cited by 43 publications
(37 citation statements)
references
References 96 publications
2
34
1
Order By: Relevance
“…The estimated coalescent ages of the predominant lineages in ST populations provide an upper bound for their divergence/contact from other groups. MSY haplogroup O2a2b1a1-Page23, equivalent to O-M117, which was previously reported to be abundant in TB groups in southwestern China and in Han Chinese (Wang et al, 2014), was dated to around ∼2.41 kya in this study. However, this MSY lineage also occurs in HM, TK, and AA populations, reflecting recent shared ancestry and/or contact (Fig.…”
Section: Discussionsupporting
confidence: 49%
See 1 more Smart Citation
“…The estimated coalescent ages of the predominant lineages in ST populations provide an upper bound for their divergence/contact from other groups. MSY haplogroup O2a2b1a1-Page23, equivalent to O-M117, which was previously reported to be abundant in TB groups in southwestern China and in Han Chinese (Wang et al, 2014), was dated to around ∼2.41 kya in this study. However, this MSY lineage also occurs in HM, TK, and AA populations, reflecting recent shared ancestry and/or contact (Fig.…”
Section: Discussionsupporting
confidence: 49%
“…Although an MSY lineage (O-M122*) was proposed to be characteristic of all modern ST populations (Su et al, 2000), subsequent studies have found further differentiation, e.g. haplogroup O2a1c-002611, which is at high frequency in Han Chinese but found at very low frequencies in Tibeto-Burman populations (Wang et al, 2013, 2014; Yan et al, 2011, 2014; Yao et al, 2017). Also, autosomal STR genotypes differentiate Tibetan and Lolo-Burmese speaking groups (Li et al, 2015; Yao et al, 2017).…”
Section: Discussionmentioning
confidence: 99%
“…This phenomenon has been observed before and was explained by selection on deleterious mutations. 27 However, owing to the better fit of genealogical rate than mutation rate with sequence-based time estimations, 25,28 we pose our time here on genealogical rate. The coalescent time of O-F444 in the Han Chinese was 7.99 ± 1.36 kya (thousand years ago).…”
Section: Resultsmentioning
confidence: 99%
“…28 The Qiangic populations might participate in the establishing of the Sino-Tibetan populations based on recent genetic evidences. 17,18,28 Detailed characterization of O-F444 may provide a broader framework of SinoTibetan populations.…”
Section: Discussionmentioning
confidence: 99%
“…Haplogroup O3a2c1*-M134 and O3a2c1a-M117 are also characteristic lineages of Han Chinese, comprising 11.4% and 16.3%, respectively910. However, another dominant paternal lineage of Han Chinese, haplogroup O3a1c-002611, is found at very low frequencies in Tibeto-Burman populations, suggesting this lineage might not have participated in the formation of Tibeto-Burman populations691011. Sex-biased admixture has also been observed during the formation of Tibeto-Burman populations.…”
mentioning
confidence: 99%